THE PARADOX OF VIRTUAL EMBODIMENT: THE BODY SCHEMA IN VIRTUAL REALITY AESTHETIC EXPERIENCE - Sara INCAO; Carlo MAZZOLA (Studia Universitatis Babeș-Bolyai. Philosophia)
New technologies implied in art creation and exhibition are modifying the traditional landmarks on which aesthetics has always focused. In particular, Virtual Reality artworks call the body into question when it comes to living a bodily experience within exhibitions accessible through technological tools that expand the human body’s capabilities and motor potential. The body's status is challenged in its traditional unity, that of a subject of experience living in a world where the spatial configuration is relatively constant. Conversely, in Virtual Reality, the spatial aspect is novel to our body which needs to adapt to unpredicted and disorientating motor schemas. Therefore, the Virtual Reality aesthetic experience takes place into a novel configuration for the human body: hybrid and split into the virtual realm.